PERAN PENDIDIKAN DALAM PEMBENTUKAN KARAKTER ANAK SEKOLAH DASAR - Kurnia Putri Maila Sari; Dian Novita; Bilqisti Imaama; Desyandri; Zelhendri Zen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the role of education in character formation in elementary school children and identify the forms of implementation and challenges faced in its implementation. Character education in elementary schools plays a strategic role because children are at the early stage of forming attitudes, values, and behaviors. This study used a qualitative approach with descriptive methods. The research subjects included elementary school teachers and students, while the research object focused on the implementation of character education in learning and school culture. Data collection techniques used observation, interviews, and documentation to obtain comprehensive data. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, using triangulation of sources and techniques to maintain data validity. The results indicate that education plays a significant role in character formation in elementary school children through teacher role models, the integration of character values ​​into the learning process, and the instillation of these values ​​through school culture and non-academic activities. The dominant character values ​​formed include discipline, responsibility, honesty, cooperation, and social awareness. Consistently implemented character education has a positive impact on students' social behavior and learning motivation. However, this study also identified several obstacles in its implementation, such as limited learning time, differences in family backgrounds, and suboptimal parental involvement. Therefore, synergy between schools, teachers, and parents is necessary for effective and sustainable implementation of character education, fostering character and noble morals in students.